Altered in vivo brain GABA and glutamate levels are associated with multiple sclerosis central fatigue. Issue 137 (April 2021) - Arm, Jameen; Oeltzschner, Georg; Al-iedani, Oun; Lea, Rod; Lechner-Scott, Jeannette; Ramadan, Saadallah
Abstract: Purpose: Fatigue is a common symptom in patients with multiple sclerosis (MS) with unknown pathophysiology. Dysfunction of the GABAergic/glutamatergic pathways involving inhibitory and excitatory neurotransmitters such as  γ-aminobutyric acid (GABA) and glutamine + glutamate pool (Glx) have been implicated in several neurological disorders. This study is aimed to evaluate the potential role of GABA and Glx in the origin of central fatigue in relapse remitting MS (RRMS) patients. Methods: 24 RRMS patients and 16 age- and sex-matched healthy controls (HC) were scanned using Mescher-Garwood point resolved spectroscopy (MEGA-PRESS) with a 3 T system to quantify GABA+ and Glx from prefrontal (PFC) and sensorimotor (SMC) cortices. Self-reported fatigue status was measured on all participants using the Modified Fatigue Impact Scale (MFIS). Results: RRMS patients had higher fatigue scores relative to HC ( p  ≤  0.05). Compared to HC, Glx levels in RRMS patients were significantly decreased in SMC ( p  =  0.04). Significant correlations were found between fatigue scores and GABA+ (r = -0.531, p  =  0.008) and Glx (r = 0.511, p  =  0.018) in PFC. Physical fatigue was negatively correlated with GABA+ in SMC and PFC (r = -0.428 and -0.472 respectively, p  ≤  0.04) and positively with PFC Glx (r = 0.480, p  =  0.028). Conclusion: The associations between fatigue and GABA + and Glx suggest that there might be dysregulation of GABAergic/glutamatergic neurotransmission in the pathophysiological mechanism of central fatigue in MS.